Effect of preoperative radiotherapy on stage IB2 and IIA2 cervical cancer: A retrospective cohort study. (June 2016) - Zhang, Tongqing; Kong, Weimin; Li, Fengshuang; Song, Dan; Liu, Tingting; Han, Chao; Jiao, Simeng; Chen, Jiao
Abstract: Introduction: The aim of the retrospective study was to investigate the therapeutic efficiency of the preoperative intracavitary radiotherapy combined with radical surgery on postoperative complications and long-term survival in patients with stage IB2 and IIA2 cervical cancer (CC). Methods: From January 1995 to December 2012, a total of 171 patients with stage IB2 or IIA2 CC were recruited into the study. They were divided into two groups according to the treatment modality provided: preoperative radiotherapy followed by radical surgery (n = 80), and radical surgery alone (n = 91). The clinical curative effect, postoperative complications and the postoperative prognosis of patients were evaluated and compared in two groups. The tumor response and survival of patients in two groups were observed in follow-up study. Results: There were no significant differences in the incidence of postoperative complications, intraoperative blood loss and surgery duration ( P  > 0.05) between the two groups. Preoperative radiotherapy did not improve the postoperative prognosis yet. Though patients undergoing preoperative radiotherapy showed the similar 1- (92.50% vs. 84.62%), 3- (85.00% vs. 81.32%) and 5-year (80.00% vs. 74.72%) survival rates, the 3- and 5-year locoregional control rates of them were much higher than those undergoing surgery alone ( P  < 0.05). Conclusion: Preoperative radiotherapy combined with radical surgery could improve locoregional control rate and would not increase the risk of postoperative complications. It may be a feasible treatment mode for early stage CC carcinoma. Highlights: Efficiency of the preoperative radiotherapy on early stage CC was evaluated. There was no difference for complication, blood loss and surgery time between two groups. Preoperative radiotherapy did not improve the postoperative pathology. 1-, 3- and 5-year survival rates were similar between two groups. 3- and 5-year locoregional control rates were much higher in radiotherapy group.